Embriogênese somática e variabilidade genética in vitro de BACURIZEIRO (Platonia insignis Mart.): uma espécie nativa da Amazônia brasileira - Marinho, Tácila Rayene dos Santos (2022)
A Brazilian Amazonian fruit, the bacurizeiro (Platonia insignis Mart.) is highly important for the sustainable development of the north and northeast regions. However, as it is in the process of domestication, its propagation techniques are still limited, so tissue culture can be an efficient biotechnological tool to achieve efficiency in the production of seedlings of this species. As it is an allogamous plant, with high genetic variability, different genotypes may not respond homogeneously to the same stimuli in vitro, so it is essential to know the genetic control of traits related to in vitro regeneration processes for the selection of more responsive genotypes. Thus, the present thesis had as general objective to develop strategies for the in vitro propagation of Platonia insignis through somatic embryogenesis from zygotic embryos, to characterize the induction process through anatomical and histochemical studies, and to study the genetic control of traits related to callogenesis, as well as the genetic variability of different accessions in the state of Maranhão. The studies carried out, and the results obtained are presented in the form of five chapters. Chapter I refer to a literature review article about the bacuri tree, its domestication process, its current propagation techniques, up to the prospection of biotechnological methodologies. In chapter III, the objective was to establish a protocol for in vitro induction and callogenesis of P. insignis Mart. The results of callogenesis induction in media without the addition of PGRs demonstrate the potential of endogenous regulators. Anatomical sections reveal high callogenesis, however not yet similar to embryogenic callus masses, therefore further investigation is needed to optimize the development of P. insignis embryonic callus. Chapter III aimed at the efficient multiplication of P. insiginis callus and the establishment of an efficient protocol for embryogenic callus regeneration. To confirm the presence of embryogenic cells, the calluses were submitted to double staining cytology. Two types of callus with different morphogenic potential were obtained: friable callus with embryogenic potential and spongy callus without embryogenic potential. In this study, the combination of 2,4-D 0.8 μm + putrescine 50 μm induced greater callus formation with embryogenic potential. In chapter IV, the genetic control of traits related to the in vitro establishment of P. insignis accessions from different regions of the state of Maranhão, Brazil was studied. The estimates of the genotypic parameters were obtained by the mixed models methodology, REML (Restricted Maximum Likelihood) /BLUP (Best Unbiased Linear Prediction) procedure. The results obtained showed high genetic variability in the population studied, in addition, accessions AC.7, AC.2, AC.1, AC.6 and AC.8 were more efficient in terms of their response to the in vitro regeneration process, presenting superior callogenesis capacity, less susceptibility to oxidation, greater ability to form roots and shoots. In chapter V, with the final considerations, we emphasize that this is the first work to research techniques for the in vitro cultivation of P. insignis through the establishment of a decontamination protocol and in vitro callogenesis induction, in addition to investigating the relationship between genetic parameters and selection of accessions responsive to in vitro regeneration. This generated knowledge will support future studies of micropropagation, conservation, and domestication of P. insignis